2005
DOI: 10.1038/sj.onc.1209024
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin 2 modulates the activity of nuclear receptor RAR β2 through activation of ERK2 kinase

Abstract: The activity of retinoid receptors activity can be regulated by various extracellular stimuli. In an effort to understand the molecular basis for this phenomenon, the role of b-arrestins was investigated. b-Arrestins constitute a class of proteins involved in the internalization of agonistactivated receptors. They have also been linked to MAPK activation suggesting a direct involvement in signaling cascades. Here, we report that b-arrestin 2 stimulates the transcriptional activation of the retinoid RAR and RXR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…This is not the first example of cell growth modulation via ␤-arr2. Indeed, it was reported recently that ␤-arr2 stimulates the transcriptional activation of retinoid RAR receptors and that the inhibition of PC12 cell growth in response to nerve growth factor involves the ␤-arr2-and ERK2-dependent transcriptional activation of the RAR-␤2 receptor (33). Together with our data, these observations suggest a possible previously unappreciated role of ␤-arrs in the control of cell division with multiple points of impact.…”
Section: Discussionsupporting
confidence: 78%
“…This is not the first example of cell growth modulation via ␤-arr2. Indeed, it was reported recently that ␤-arr2 stimulates the transcriptional activation of retinoid RAR receptors and that the inhibition of PC12 cell growth in response to nerve growth factor involves the ␤-arr2-and ERK2-dependent transcriptional activation of the RAR-␤2 receptor (33). Together with our data, these observations suggest a possible previously unappreciated role of ␤-arrs in the control of cell division with multiple points of impact.…”
Section: Discussionsupporting
confidence: 78%
“…As the turnover of retinoid receptors is regulated by their phosphorylation status, it is plausible that in this study, decreased expression of these receptors might be due to their aberrant phosphorylation status by MAPKs. A recent report by Piu et al (30) shows that RARh2 is phosphorylated by extracellular signal-regulated kinase 2; second, in various cancers including melanoma loss of RARh, expression has been correlated to the hypermethylated status of RARh promoter (31) and/or to a deficient acetylation of histones (32), which in both cases result in repressed chromatin. Apparently, the presence of an epigenetically silent RARh2 promoter correlates with the lack of RARa and causes resistance to the growthinhibitory effect of retinoic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Piu and colleagues have demonstrated that ␤-arrestin 2 enhances the transcriptional activity of the nuclear receptor RAR-␤2 and this effect is dependent upon the recruitment of ERK2 and its direct interaction with RAR-␤2 in the cytoplasm (Piu et al, 2006). ␤-arrestin-2-dependent p38 activation provides another example.…”
Section: Regulation Of Subcellular Compartmentalization Of Mapksmentioning
confidence: 99%